Edukasi Self-Massage Release bagi Wanita Karir untuk Mendukung Kesehatan dan Produktivitas Kerja - Mitsalina, Dinan; Mylsidayu, Apta; Yuliasih, Yuliasih; Oktafiranda, Nadya Dwi; Yuliana, Ela; Diyananda, Dzulfiqar (Jurnal Abdimas Kesehatan (JAK), 2025)
The demands of multitasking and dual roles make career women vulnerable to musculoskeletal (MSK) complaints and psychosocial fatigue. Self-Massage Release (SMR), as a form of Self-Myofascial Release, has the potential to be a safe, affordable, and applicable self-intervention. This study evaluated the effectiveness of SMR education based on participatory andragogy in a community of athlete parents at the “I Can Gymnastic” Artistic Gymnastics Club, East Jakarta (June 26, 2025; n=20; aged 30–40 years). The intervention included baseline assessment, theoretical presentation, demonstration (manual/fingers, tennis ball, foam roller), practice with guided correction, and reflection–evaluation. Pre–post assessments covered knowledge/skills, pain (VAS), MSK complaints (NMQ), and work productivity (WHO-HPQ-SF). At baseline, 85% of participants reported mild–moderate pain/stiffness and 70% had never practiced SMR. Post-program, 93% could explain SMR benefits and 87% demonstrated correct techniques, showing effective transfer of knowledge and psychomotor skills. NMQ complaints decreased in the trunk and upper limbs (especially lower/upper back, neck, shoulders), mean VAS decreased from 6.2 to 3.1 with the greatest reduction in neck and shoulders, and productivity increased from 72% to 86% (+14 points), indicating a shift from passive (medication/rest) to active-preventive strategies. These findings confirm that community-based SMR education with paired practice and guided correction is effective, applicable, and replicable as an empowering, low-cost, and sustainable health approach for career women. Future studies should conduct controlled trials with larger participants, longer follow-up, objective movement/ muscle function measures, and cost–benefit analysis for productivity outcomes.